DINAMIKA GERAKAN MUHAMMADIYAH JAWA DAN SUMATERA BARAT: ANALISIS HISTORIS, KULTURAL, DAN STRUKTURAL - Bukhari Bukhari; Almawadi Almawadi; Ahmad Lahmi; Mursal Mursal (Ensiklopedia Research and Community Service Review, 2026)
This article analyzes the dynamics of the Muhammadiyah movement in Java and West Sumatra by highlighting the historical, cultural, and structural differences that shape the character of the movement in both regions. Although Muhammadiyah promotes a normatively uniform ideology of Islamic modernism, its practices and expressions at the local level exhibit significant variation. This study employs a qualitative approach with a comparative-historical design based on library research. Data are drawn from official Muhammadiyah documents, works of key figures and scholars, and relevant academic literature, and are analyzed qualitatively using the theoretical framework of Islamic modernism, structuration theory, and the concept of cultural negotiation.The findings indicate that Muhammadiyah in Java developed within a cultural context that emphasizes harmony and a hierarchical social structure, resulting in a movement characterized by moderation, persuasive strategies, and gradual change, with institutional strengthening as its primary approach. In contrast, Muhammadiyah in West Sumatra evolved within an egalitarian culture and a critical surau-based intellectual tradition, producing a movement that is more rational, assertive, and argumentative. These differences are not dichotomous; rather, they represent a spectrum of complementary expressions of Muhammadiyah’s Islamic modernism.This study demonstrates that the strength of Muhammadiyah as a national Islamic movement lies in its ability to manage local diversity without losing its ideological identity. The article contributes to the study of modern Islam in Indonesia by emphasizing the importance of contextual approaches in understanding the dynamics of religious movements.Keywords: Muhammadiyah, Islamic modernism, Java, West Sumatra, cultural dynamics.